STRATEGI PEMBELAJARAN MENGGUNAKAN MEDIA DADU SEHAT SEBAGAI UPAYA DALAM MENINGKATKAN KEMAMPUAN BERNYANYI SISWA KELAS IX DI SMPN 51 SURABAYA - Damar Trisna Asih; Setyo Yanuartuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning Strategy is a series of activities carried out to achieve learning objectives. A teacher certainly has different learning strategies in implementing learning in the classroom, especially Arts and Culture learning strategies which must apply creative and interactive principles. Arts and Culture subjects generally consist of practical material, so they are considered to have their own challenges and difficulties to be done easily. So learning media is needed as a tool to help a teacher in delivering material. The purpose of using learning media is to facilitate the delivery of material by teachers to students. Apart from that, using creative and interactive learning media can help students' social and emotional emotions to create a pleasant classroom atmosphere. Of course, feeling happy, not boring, and students tending to be active in using learning media, will help carry out effective learning activities, including easily achieving learning goals. Thus, this research aims to explain how learning strategies use healthy dice media as an effort to improve the singing abilities of class IX students at SMPN 51 Surabaya. This research uses a descriptive qualitative research method, namely research that produces data in the form of descriptive answers in the form of words based on the results of observations. The results of this research are how to implement learning strategies using healthy Dice Media and the results of implementing learning using healthy Dice Media in improving the singing ability of class IX students at SMPN 51 Surabaya.